The process of professionalization of the Army of Alto Peru during the wars of Independence (Quinto Sol, 2011)
The Formation of a temporary Board of government in Buenos Aires city in May of 1810 was the beginning of a process that would end with the independence from the Spanish crown of the territories that made up the viceroyalty of Río de la Plata. The Auxiliary Army of Peru was one of the main tools the new authorities had in order to face an inevitable phenomenon: war. Argentine historiography has shown that, after the defeats in Alto Peru and Paraguay, the armies would be subject of professionalization. The goal of this article is to show what this professionalization process looked like, trying to visualize the different aims as well as the limits experienced.
Keywords: war; Army; professionalization; officials; troops